2020
DOI: 10.3856/vol48-issue3-fulltext-2434
|View full text |Cite
|
Sign up to set email alerts
|

Incidental catch of marine organisms registered in the Chilean Antarctic krill fishery, years 2012-2016

Abstract: Krill (Euphausia superba) catch is currently the most relevant fishery industry in Antarctic waters. This resource is a keystone species in the Antarctic food web, sustaining the contribution to the trophic ecology of many invertebrate and vertebrate species. To catch krill, part of the fleet in this fishery uses large mid-water nets that also retain a diversity of other organisms like plankton, meroplankton, and fish species as bycatch. Therefore, it is necessary to understand and evaluate the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Reductions in the rate of pinniped entanglement were observed on three vessels, with entanglement rates ranging from 1.38 to 5.5 animals/haul before excluder use and from 0 to 0.23 animals/haul when excluders were employed (Hooper et al 2005). Observer data from a Chilean krill fishing vessel equipped with a pinniped exclusion net and operating from 2012 to 2016 showed that entanglement occurred during 1.13% of monitored hauls ( n = 791), but 22.2% of those entanglements were lethal (Arana & Rolleri 2020). Additional incidental mortalities of AFS entangled in trawls with excluder devices have been reported by CCAMLR (2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in the rate of pinniped entanglement were observed on three vessels, with entanglement rates ranging from 1.38 to 5.5 animals/haul before excluder use and from 0 to 0.23 animals/haul when excluders were employed (Hooper et al 2005). Observer data from a Chilean krill fishing vessel equipped with a pinniped exclusion net and operating from 2012 to 2016 showed that entanglement occurred during 1.13% of monitored hauls ( n = 791), but 22.2% of those entanglements were lethal (Arana & Rolleri 2020). Additional incidental mortalities of AFS entangled in trawls with excluder devices have been reported by CCAMLR (2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is agreement on the need to improve data quality and observer coverage for reporting from the krill fishery (e.g. Arana & Rolleri 2020). However, a comprehensive review of marine mammal and seabird interactions with the krill fishery is also needed because the likelihood of entanglement in trawl nets varies greatly depending on the location, vessel, gear type, and time of year.…”
Section: Discussionmentioning
confidence: 99%
“…For the 2018/19 season, fishing for toothfish and other fin-fish was still prohibited in subarea 48.1 with exceptions for research purposes (CCAMLR, 2018). Subarea 48.1 at time of writing was mainly used for krill (Euphausiacea) fisheries via midwater trawling, where macrourids are not common by-catch (Watters, 1996;Arana and Rolleri, 2020). Although, the three carcasses are unlikely to originate from krill fishery by-catch, it is possible that they resulted from fisheries, in particular since fishing vessels were present close to the study location on the day the carcasses were found (Figure 1).…”
Section: A B E D Cmentioning
confidence: 99%